Designing Calorimeter Made from Various Wastes - Farida, Ida; Akbar, Gilang Saeful; Aisyah, Riri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
A research has been conducted which aims to design a waste-based calorimeter as an alternative to measuring heat for chemistry practicum in schools. Research products developed through the steps of design-based research comprising the steps of analysis, design, and development. The resulting product is a waste-based calorimeter equipped with an automatic stirrer. The container to store the reagent solution on the calorimeter is made of Styrofoam, paper, plastic, melamine, PVC and bamboo. Optimization tool was conducted to determine the heat capacity of the calorimeter and the enthalpy of neutralization. The highest accuracy calorimeter value between 78-97%. Bamboo calorimeter has the highest accuracy value (97%). Styrofoam calorimeter has the lowest accuracy values (78%). Based on the results of the validation and feasibility test it can be concluded that the product is declared valid and feasible.